Diseño de una célula de producción simulada para prácticas experimentales de los estudiantes de Ingeniería Industrial. - Núñez Acosta, Alvaro Paúl (2020)
The purpose of this research project is the "Design of a simulated production cell for experimental practices of Industrial Engineering students" to develop new skills in university students. These will be useful for the fulfillment of the activities within the labor field. The main objective of the project aims to the design of workstations that will make up a production cell through the use of a design and simulation software. This study is presented as descriptive research as it is based on the collection of information from various bibliography sources. The observational research technique was adopted, which allowed the evaluation of the different elements that are required for the design of a manufacturing cell and its simulation. Through information gathering about manufacturing cells, the processes involved -cell manufacturing systems immersed in the productive industry- contribute to the improvement of the quality of the products generated in Ecuador. This information is oriented to the learning process of the students using a simulation model of a system that allows its manipulation showing the possible results that can be obtained through the use of software programs. These help the user decide which variables will be applied; the methods that will be used to the data collection, the interpretation of the results obtained which favor the application of the theoretical knowledge acquired throughout the career. The importance of the development of experimental practices is also vital since through them measures are established and taken. The result allows users to verify or prove theories right. This generates professionals who provide new and innovative ideas for the solution of problems.